Biosignal Classification and Disease Prediction with Deep Learning [Derin Öǧrenme ile Biyosinyal Siniflandirma ve Hastalik Tahmini] - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2020)
Artificial intelligence is developing in every field. One of these areas is health. Along with the technological developments, artificial intelligence has started to take an important place in the field of health. In this way, artificial intelligence for the detection and diagnosis of diseases at an early stage facilitates the work of doctors and patients. Artificial intelligence was used in this study for the early diagnosis of heart diseases. Artificial intelligence consists of artificial neural networks that consist of many layers. Artificial neural networks predict the classes of inputs by converting the inputs to outputs. Convolutional neural network was used in this study. Convolutional neural network is used to classify the objects in the image. The artificial neural network used in the study was first trained with normal and sick heart sounds and the result of this training was tested. As a result of the tests carried out, it has been seen that trained artificial intelligence distinguishes between normal and sick heart sounds. © 2020 IEEE.
Keywords: artificial intelligence; classification; deep learning; disease; heart; predict